2013
DOI: 10.1063/1.4848675
|View full text |Cite
|
Sign up to set email alerts
|

A transferable coarse-grained model for diphenylalanine: How to represent an environment driven conformational transition

Abstract: One of the major challenges in the development of coarse grained (CG) simulation models that aim at biomolecular structure formation processes is the correct representation of an environment-driven conformational change, for example, a folding/unfolding event upon interaction with an interface or upon aggregation. In the present study, we investigate this transferability challenge for a CG model using the example of diphenylalanine. This dipeptide displays a transition from a trans-like to a cis-like conformat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
28
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 71 publications
5
28
0
Order By: Relevance
“…The stabilization of a specific conformation in the aggregate—in the present case the α -helix—due to contact with a hydrophobic surface presented by neighboring peptides can also be observed in other systems. For example in diphenylalanine in solution, a conformational transition is observed upon aggregation: in bulk water the molecule adopts a trans-like state, but the molecular interface provided by the surrounding molecules in an aggregate triggers the conformational transition to a cis-like state so that the hydrophobic phenylalanine side chains can get in contact with hydrophobic patches on the surface [ 33 ].…”
Section: Resultsmentioning
confidence: 99%
“…The stabilization of a specific conformation in the aggregate—in the present case the α -helix—due to contact with a hydrophobic surface presented by neighboring peptides can also be observed in other systems. For example in diphenylalanine in solution, a conformational transition is observed upon aggregation: in bulk water the molecule adopts a trans-like state, but the molecular interface provided by the surrounding molecules in an aggregate triggers the conformational transition to a cis-like state so that the hydrophobic phenylalanine side chains can get in contact with hydrophobic patches on the surface [ 33 ].…”
Section: Resultsmentioning
confidence: 99%
“…Given the general difficulty in CG parameterization of peptides placed at lipid-water interfaces, 67 we reasoned that the octane/water interface and/or the combination of this and the terminal Trp residues was related to the high dimerization propensity of the CG systems. The structures of water/lipid/peptide termini were also thought to affect the CG results, as suggested by the SWL21 and GWL21 results; attachment of one residue caused marked changes.…”
Section: The Cg Model Showed a Greater Tendency For Dimerization Thanmentioning
confidence: 99%
“…Apart from the reduction in the total number of particles, the interaction potentials get simplified because the potential energy surface becomes smoother leading to the acceleration of the system dynamics . CG methods have been effectively used in the past to study biological systems, polymer dynamics,,, ionic liquids, and liquid crystalline compounds. There are various CG methods proposed in the literature depending upon the accuracy, level of CG, and simplification of the potential energy surface, and one determines the method of coarse‐graining depending upon the properties they aim to reproduce.…”
Section: Introductionmentioning
confidence: 99%
“…For liquid ethylbenzene there was instead the need of the modification by a temperature factor of T/T0 ( T 0 is the temperature at which the CG potentials were developed and T is the working temperature). Dalgicdir et al have studied the transferability of CG model for diphenylalanine peptide in two different chemical environments. They showed that one single CG model can reproduce conformations of diphenylalanine dipeptides in both the bulk and interface (cyclohexane/water) and the partitioning in hydrophobic/hydrophilic medium.…”
Section: Introductionmentioning
confidence: 99%